Opioid free anesthesia in a pre-term neonate: A case report - Kakkar, Mahak; Jain, Swati; Bathla, Sapna; Bamba, Charu (Indian Journal of Case Reports, 2019)
Opioids play a major role in the perioperative management of pain in adults and children. Though there is significant morbidity and mortality associated with overdosage of opioids, they remain the most common means of providing analgesia in the perioperative period. We report the case of a preterm neonate born with low birth weight who underwent high sigmoid loop colostomy for high anorectal malformation using opioid-free general anesthesia with supplementation with caudal block. Successful uncomplicated extubation of preterm baby was achieved with good spontaneous efforts. Opioid free general anesthesia can prevent respiratory depression and the need for postoperative mechanical ventilation even when given to preterm neonates.